Stjórnlagaráð, saga þess og hlutverk - Sigurður Hólmar Kristjánsson 1972- (2012)
Verkefnið er lokað til 11.5.2022. Although a proposal for the establishment of a Constitutional Assembly was first submitted to Parliament in 1948, the idea can be traced all the way back to 1851. Then, a national meeting (þjóðfundur) was held following a promise made by Frederick VII, King of Denmark, that such meeting was to be held in Iceland. Following the economic collapse in 2008-9, a demand for a revision of the Icelandic political system was prominent. A part of that demand was for a revision of the 1944 Constitution. With the Act no. 90/2010 passed by the Icelandic government June 16th 2010 it was decided to convene an advisory Constitutional Assembly (stjórnlagaþing) to review the Constitution of the republic of Iceland, no. 33/1944. At the end of its term the Assembly should submit to the Parliament a draft constitutional law ready for Parliamentary treatment. Elections for the Constitutional Assembly took place on November 27 2010, where 25 delegates were elected to serve as Assembly members. The Assembly, however, was not able to operate as planned, as three individuals appealed the implementation of the election. After evaluating the circumstances of the case, the Supreme Court of Iceland concluded that the implementation of the elections had been flawed to such a degree that the result should be annulled. To ensure that the review process proceeded as planned, the majority of Parliament appointed a Constitutional Council (stjórnlagaráð) to take over the task of the Constitutional Assembly. Based on that decision, the Constitutional Council commenced operations April 6th 2011. On July 29th 2011 the Constitutional Council handed a draft bill to the Parliament for consideration. Loud debates in Parliament have been on how to handle the draft bill from the constitutional council, especially on whether the proposed bill should be submitted unchanged to the nation and a referendum held.